Estudo da infiltração marginal em restaurações de resinas compostas para dentes posteriores: efeito de material, preparo cavitário e condicionamento do esmalte a nível cervical - Araújo, Rosehelene Marotta [UNESP] (Universidade Estadual Paulista (Unesp), 1989)
For many years the dental profession has sought an esthetic material to replace the amalgam alloys. Recently composite resins for posterior teeth have been introduced into the marketplace. The manufacturers claimed that these materials are indicated for stress-bearing restoration. However. such resins have presented some limitations such as marginal leakage which has great clinical importance because it is responsible for postoperative sensitivity, and occurence of secundary caries followed by pathological changes of the pulp. The purpose of this ''in vitro'' study was to investigate the cervical marginal leakage in class II restorations with chemically cured resin - PlO - and light- cured resin - P30 - in two types of cavities: conventional and adhesive. The effect of acid-etching in this area was also observed. The cavities were prepared in premolar teeth, recently extracted for orthodontic purposes, using a Microscope Modified by GABRIELLI and cols.25, in order to obtain standardized cavities. Dentine adhesive (Scotchbond) was used in all experimental groups Leakage was evidenced by Rodamina B dye penetration after thermocycling procedure between 10°C and 50ºC temperature and analysed according to HIRSCH g WEINREB modified criterion by using ZEISS Stereoscopic Magnifying Glass (10x). According to the results, we should concluded that: 1- Cervical marginal leakage occurred to 77,5% of conventional cavities restorations and 47,5% of adhesives cavities. 2- The major percents of leakage, regardless the factors studied, always occurred at level 3, that is, with leakage up to axial wall. 3- Either chemically cured resin or light – cured resin presented the same leakage. 4- The acid-etching reduced from 70% to 55% the leakage percentage observed. 5- The leakage observed for adhesive or conventional cavities continued when chemically cured resin or light- cured resin was used. 6- Acid-etching...

Por muitos anos a profissão odontológica tem procurado um material estético para substituir as ligas de amálgama. Recentemente, têm aparecido no comércio as resinas compostas para dentes posteriores indicadas para restaurações onde não há incidência de forças mastigatórias. Tais resinas têm, porém, apresentado falhas, e, entre elas, a infiltração marginal, que tem enorme importância, pois é responsável pela sensibilidade pós-operatória, manchamento e ocorrência de cáries secundárias com consequentes alterações patológicas da polpa. Este trabalho teve a finalidade de estudar ''in vitro'' a infiltração marginal, a nível cervical, de restaurações classe II com as resinas posteriores quimicamente ativadas P10 e fotoativadas P30, em dois tipos de cavidades: convencional e adesiva. Foi verificado também o efeito do condicionamento ácido nesta região. A pesquisa foi realizada em dentes pré-molares recentemente extraídos por motivo ortodôntico, e para obter cavidades padronizadas os preparos foram feitos com a utilização de um microscópio modificado por GABRIELLI e cols.25 Foi utilizado adesivo dentinário (Scotchbond) em todos grupos experimentais. A infiltração foi evidenciada por meio do corante Rodamina B, após ciclagem térmica entre as temperaturas 10°C e 50°C, e analisada seguindo o critério de HIRSCH e WEINREB37, modificado, com auxílio de uma lupa estereoscópica ZEISS com 10 aumentos. Pelos resultados obtidos, pudemos verificar que: 1- Ocorreu infiltração marginal a nível cervical em 77,5% das restaurações de cavidades convencionais e em 47,5% das cavidades adesivas. 2- A maior percentagem de infiltração, independentemente dos fatores em estudo, ocorreu sempre no nível 3, ou seja, com infiltração até a parede axial. 3- Tanto a resina quimicamente ativada quanto a fotoativada permitiram a mesma infiltração. 4- O condicionamento ...
Keywords: Obturações (Odontologia); Resinas dentarias; Infiltração dentária; Resinas compostas; Fillings (Dentistry)